The cost-effectiveness of hypertonic saline inhalations for infant bronchiolitis - Jefferson Antonio Buendía; Ranniery Acuña-Cordero (BMC, 2020)
Abstract Background Pharmacological treatment for bronchiolitis is primarily supportive because bronchodilators, steroids, and antibiotics, show little benefit. Clinical studies have suggested that nebulized 3% hypertonic solution is useful for infants with bronchiolitis. This study aims to evaluate the cost-effectiveness of the HS inhalations in infant bronchiolitis in a tropical country. Methods Decision tree analysis was used to calculate the expected costs and QALYs. All cost and use of resources were collected directly from medical invoices of 193 patient hospitalized with diagnosis of bronchiolitis in tertiary centers, of Rionegro, Colombia. The utility values applied to QALYs calculations were collected from the literature. The economic analysis was carried out from a societal perspective. Results The model showed that nebulized 3% hypertonic solution, was associated with lower total cost than controls (US $200vs US $240 average cost per patient), and higher QALYs (0.92 vs 0.91 average per patient); showing dominance. A position of dominance negates the need to calculate an incremental cost-effectiveness ratio. Conclusion The nebulized 3% hypertonic solution was cost-effective in the inpatient treatment of infant bronchiolitis. Our study provides evidence that should be used by decision-makers to improve clinical practice guidelines and should be replicated to validate their results in other tropical countries.